LDL-C augments whereas HDL-C prevents inflammatory innate immune memory - Sohrabi, Yahya; Schwarz, Dennis; Reinecke, Holger (Trends in molecular medicine, 2022)
Recent studies emphasize the importance of low-density lipoprotein cholesterol (LDL-C) in altering the hematopoietic cell compartment of bone marrow and of high-density lipoprotein cholesterol (HDL-C) in inhibiting metabolic endotoxemia-induced inflammation. The data suggest that these lipoproteins may exert their inflammatory or anti-inflammatory roles by modulating innate immune memory. Targeting specific LDL-C and HDL-C subfractions could therefore potentially reduce the residual risk in hepatic and cardiometabolic disease.
Keywords: Immunity, Innate; Immunologic Memory; Inflammation; Humans; imunologická paměť; inflammation; přirozená imunita; lidé; zánět; atherosclerosis; cholesterol; innate immune memory; liver; LDL-cholesterol; endotoxemia; Cholesterol, LDL; HDL-cholesterol; Cholesterol, HDL